A study to assess the level of anxiety related to childbirth among primi antenatal women in selected hospitals, Bangalore - A. JEBARNA KIRUBA MARY,; FATHIMA LATHEEF, (International Journal of Pharma and Bio Sciences, 2017)
The present study has been conducted with the aim of assessing the level of anxiety related to childbirth among Primi antenatal women in selected Hospitals, Bangalore. A Quantitative approach was adopted for the study. The research design chosen for the study was descriptive. 30 Primi antenatal women who were on the first trimester of pregnancy and who met the inclusion criteria in selected hospitals, Banglore were selected through convenient sampling. Wijma Delivery Expectancy Questionnaire (W-DEQ Version-A) was used to assess the level of anxiety related to childbirth. Descriptive statistics were used to present the findings of the study. 53% of the samples had Mild fear of childbirth in first trimester and 20% had severe fear of childbirth in second trimester. But in the third trimester majority of Primi antenatal women (i.e.) 73% had clinical fear of childbirth, 17% had severe fear of childbirth and 7% had moderate fear of childbirth.Throughout the course of pregnancy, higher level of anxiety related to childbirth was reported during their third trimester of pregnancy. Anxiety associated with childbirth has serious consequences. Findings suggest the need of the training programme of mind body interventions as an intervention for Primi antenatal women to reduce the anxiety related to childbirth and prevent its consequences.